Preliminary Study of Metals Concentration in Bivalves Collected from Natural Habitats, Local Wet Markets and Street Stalls around Kuching and Samarahan Region - Masania, Mohd Basri (Universiti Malaysia Sarawak (UNIMAS), 2014)
Bivalves from the species Solen regularis, Polymesoda expansa and Anadara granosa are the regularly consumed by local peoples in Kuching and Samarahan region. The three bivalves samples from natural habitat (including water and sediment), local wet markets and street stalls were collected. Atomic Absorption Spectrophotometer (AAS) were used to analysed cadmium (Cd), chromium (Cr), copper (Cu), lead (Ph), and zinc (Zn) while Flow Injection Mercury System (FIMS) for mercury (lIg). Highest metals concentration; Cr (22.73±O.74 IJ.glg) detected from tissues of P. expansa from Kota Samaraban Roundabout, en (l1.82±O.83 IJ.glg) detected from shells ofS. regularis from Jalan Liu Shan Bang, Hg (O.0444±O.OOOI IJ.glg) detected from tissues ofP. expansa from Sungai Melaban and Zn (754.00±:22.05 IJ.glg) detected from tissues of P. expansa from Kota Samaraban Roundabout. Cd and Ph in all samples were below detection limit of AAS. When compared with the permissible limit set by FAOIWHO 2012, Zn concentration was exceed the permissible limit while Cu and Hg were below permissible limit for most bivalves samples. The bioaccumulation factor (BAFs) of both tissue and shell ofP. expansa was Hg>Zn, while tissues and shells of S. regularis showing that Zn>Hg>Cr and BAFs for tissues ofA. granosa was Zn>Hg and shell Hg>Zn.